Penyampaian Khotbah Melalui Media Live Streaming Sebagai Upaya Membangun Spiritualitas di Era Digital - Hondro, Menas Misahati; Andi Yusuf, Etni Grace (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
This study aims to examine the use of live streaming sermons as an effort to build congregational spirituality. This study uses a literature study method to explore the urgency of sermons in strengthening the faith and spirituality of congregations, especially in the era of digital society. Through a review of various studies, this article presents two important aspects: first, the role of sermons in shaping a deeper understanding and practice of spirituality, and second, the church's response to changes in the social and technological context, including the phenomenon of live streaming sermons. The importance of sermons in guiding, inspiring, and deepening the faith of congregations is evident in various studies that highlight their positive effects in building spirituality, both in the millennial and Z generations and in Christians in general. Meanwhile, the church's adaptation to technological challenges has given rise to the phenomenon of live streaming sermons, which offer new flexibility and accessibility in worship, but also raise considerations related to personal interaction and the sustainability of the values of the spiritual community. In this context, this article emphasizes that sermons remain a vital instrument in building Christian spirituality, while adaptation to changes in the times and technology is a challenge that must be overcome wisely. Thus, sermons are not only a means of conveying spiritual messages, but also an opportunity to deepen the worship experience and expand the reach of church services in this digital era.AbstrakPenelitian ini bertujuan untuk meneliti penggunaan khotbah live streaming dalam sebagai upaya membangun spiritualitas jemaat. Penelitian ini menggunakan metode studi kepustakaan untuk mengeksplorasi urgensi khotbah dalam memperkuat iman dan spiritualitas jemaat, terutama dalam era masyarakat digital. Melalui tinjauan terhadap berbagai penelitian, artikel ini menyajikan dua aspek penting: pertama, peran khotbah dalam membentuk pemahaman dan praktek spiritualitas yang lebih dalam, dan kedua, respons gereja terhadap perubahan konteks sosial dan teknologi, termasuk fenomena khotbah live streaming. Pentingnya khotbah dalam membimbing, menginspirasi, dan memperdalam iman jemaat terbukti dalam berbagai penelitian yang menyoroti efek positifnya dalam membangun spiritualitas, baik pada generasi milenial dan Z maupun pada umat Kristen pada umumnya. Sementara itu, adaptasi gereja terhadap tantangan teknologi memunculkan fenomena khotbah live streaming, yang menawarkan fleksibilitas dan aksesibilitas baru dalam ibadah, tetapi juga menimbulkan pertimbangan terkait dengan interaksi personal dan keberlangsungan nilai-nilai komunitas rohani. Dalam konteks ini, artikel ini menegaskan bahwa khotbah tetap menjadi instrumen vital dalam membangun spiritualitas umat Kristen, sementara adaptasi terhadap perubahan zaman dan teknologi menjadi tantangan yang harus diatasi dengan bijak. Dengan demikian, khotbah bukan hanya sekadar sarana penyampaian pesan rohani, tetapi juga peluang untuk memperdalam pengalaman ibadah dan memperluas jangkauan pelayanan gereja di era digital ini.